2001
DOI: 10.1086/322602
|View full text |Cite
|
Sign up to set email alerts
|

Fever in Returned Travelers: Review of Hospital Admissions for a 3‐Year Period

Abstract: We reviewed 232 consecutive patients admitted to a tertiary-care hospital under the care of an infectious diseases unit for management of febrile illness acquired overseas. A total of 53% presented to hospital within 1 week of return and 96% within 6 months. Malaria was the most common diagnosis (27% of patients), followed by respiratory tract infection (24%), gastroenteritis (14%), dengue fever (8%), and bacterial pneumonia (6%). Pretravel vaccination may have prevented a number of admissions, including influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
105
3
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(113 citation statements)
references
References 22 publications
3
105
3
2
Order By: Relevance
“…Previous studies have reported a low prevalence of typhoid and paratyphoid among travellers to North Africa; however, for travellers planning to remain in the region for six months or longer, vaccination against typhoid is recommended by the WHO and the CDC (http://www.who.int/ith/en/ and http://wwwn.cdc.gov/travel/). An Australian study [49] reviewed 232 patients (15% travelled to Africa) admitted to a tertiary-care hospital for management of febrile illness acquired overseas. Typhoid fever was found in eight (3.5%) patients and was more common in travellers returning from a trip to Asia.…”
Section: Typhoid and Paratyphoid Fever In Travellers To North Africamentioning
confidence: 99%
“…Previous studies have reported a low prevalence of typhoid and paratyphoid among travellers to North Africa; however, for travellers planning to remain in the region for six months or longer, vaccination against typhoid is recommended by the WHO and the CDC (http://www.who.int/ith/en/ and http://wwwn.cdc.gov/travel/). An Australian study [49] reviewed 232 patients (15% travelled to Africa) admitted to a tertiary-care hospital for management of febrile illness acquired overseas. Typhoid fever was found in eight (3.5%) patients and was more common in travellers returning from a trip to Asia.…”
Section: Typhoid and Paratyphoid Fever In Travellers To North Africamentioning
confidence: 99%
“…For these tourists returning home, imported fevers are a common occurrence and rickettsial infections are a relatively frequent contributor (2-3.3% of all imported fevers). [5][6][7] Rickettsial infections ranked fourth among the identifiable causes of systemic febrile illness in returned travelers from Southeast Asia (16 [2.9%] of 547 identified etiologies). 8 Detailed epidemiology and understanding on the burden of rickettsioses in Southeast Asia has been limited.…”
Section: Introductionmentioning
confidence: 99%
“…A study of febrile illnesses in travelers returning to Australia reported only 27z of diagnoses were malaria, followed by respiratory tract infection (24z), gastroenteritis (14z), dengue fever (8z), and bacterial pneumonia (6z) (18). In India, 88z of patients with acute fever tested for malaria did not have evidence of malaria by light microscopy or malaria RDTs (9).…”
mentioning
confidence: 99%
“…In Ethiopia, fewer than 20z of malaria infections are confirmed by laboratory methods; the remainder is diagnosed through clinical histories and examinations. Clinicians almost invariably respond to positive malaria tests by prescribing antimalarials but often ignore negative test results and prescribe antimalarials anyway (18). When diagnostic facilities are available, more than half of patients with negative test results are still treated for malaria (19,20).…”
mentioning
confidence: 99%